The impact of service quality and activity on visitors' satisfaction: A study on tourism industry in Sarawak (Damai Puri Resort, Sematan Palm Beach Resort, & One Hotel Santubong) - Pui, Derrick Len Khan (Universiti Malaysia Sarawak (UNIMAS), 2013)
Tourism means to travel for recreational, leisure or business purposes. The World Tourism Organization (1995) defmes tourists as people "traveling and staying in places outside their usual environment for not more than one consecutive year for leisure, business and other purposes. Besides that, Bennett (2000), states that tourism is a people temporarily traveling to destinations apart from the places where they live, work, and also the activities during their stay at those destinations>,"The changes in the Malaysian lifestyle has caused much industrialization and urbanization in major parts of Malaysia which creates an atmosphere that is full of pollution and stress like traffic jams, therefore Malaysian would prefer to retreat to these destinations just to relax and have fun. Thus, many Malaysians realized the importance of getting away from all the hustle and bustle of life to a much peaceful place as a source for enjoyment in a relaxing environment, which encourage them to take trips to visit other places (Stecker, 1996).